2020
DOI: 10.1177/2049936120959561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating appropriateness and diagnostic stewardship opportunities of multiplex polymerase chain reaction gastrointestinal testing within a hospital system

Abstract: Objective: This single-center, retrospective, observational cohort study evaluates the appropriateness of the BioFire® FilmArray® Gastrointestinal (GI) multiplex PCR panel testing at a community-teaching hospital. Methods: All adult, hospitalized patients at Prisma Health Richland Hospital with a documented GI multiplex PCR panel from 1 April 2015 through 28 February 2018 were included in the analysis. Inappropriate use of the GI panel was defined as a test obtained without documented diarrhea, greater than 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
2
15
1
Order By: Relevance
“…Unfortunately, rapid diagnostics have not always had a clear positive impact on clinical outcomes and antibiotic use, leaving the optimal utilization of these tests unclear. 76 81 Misuse and overuse of diagnostics have their own potential for untoward costs and outcomes. Some tests may reduce need for additional diagnostics, like imaging or endoscopic procedures; however, they also may have a negative financial impact if no action is taken based on the results or the tests are inappropriately ordered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, rapid diagnostics have not always had a clear positive impact on clinical outcomes and antibiotic use, leaving the optimal utilization of these tests unclear. 76 81 Misuse and overuse of diagnostics have their own potential for untoward costs and outcomes. Some tests may reduce need for additional diagnostics, like imaging or endoscopic procedures; however, they also may have a negative financial impact if no action is taken based on the results or the tests are inappropriately ordered.…”
Section: Discussionmentioning
confidence: 99%
“…Some tests may reduce need for additional diagnostics, like imaging or endoscopic procedures; however, they also may have a negative financial impact if no action is taken based on the results or the tests are inappropriately ordered. 76 81 In addition, PCR based tests cannot distinguish infection or disease from colonization; therefore, clinical context should be considered, and pre-test probability should be high before ordering these panels. Both fungal and syndromic tests should be targeted to appropriate clinical syndromes and broad ‘shotgun-like’ approaches should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that diagnosing infectious gastroenteritis with a multiplex PCR panel-based approach resulted in reduced usage of antibiotics. O'Neal et al 16 examined the initiation of antibiotics among patients who had undergone multiplex PCR gastrointestinal panel-based tests at a community teaching hospital. They showed that patients with negative test results were started on antibiotics significantly less frequently than patients with positive test results (62.5% versus 80.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, early identification may rule out infectious etiologies, prompting earlier initiation of treatments such as adjusting immunosuppressive dosing or changing medications. However, the utility of multiplex PCR testing may be limited due to an increased risk of incidental findings in SOT patients who have been hospitalized longer, particularly >48–72 h 37,38 . Several diagnostic stewardship approaches may be useful for multiplex PCRs.…”
Section: Rapid Molecular Diagnosticsmentioning
confidence: 99%